Public health in China: An environmental and socio-economic perspective. (March 2016) - Song, Wenjing; Li, Yonghua; Hao, Zhe; Li, Hairong; Wang, Wuyi
Abstract: Despite the large literature on public health, few studies have examined the associations between public health outcomes and environmental and socio-economic factors. This study bridges this gap by demonstrating the relationships between public health and 10 selected environmental and socio-economic factors from the spatial perspective. In particular, three public health outcomes in China are investigated, namely the number of centenarians per 100, 000 people (termed the centenarian ratio), the proportion of nonagenarians of the 65 years and older population (termed the longevity index), and life expectancy at birth. We base our analysis on stepwise regression and geographically weighted regression models, with study areas of 31 provinces in China. Our results show that SO2 (sulfur dioxide) concentration decreases the centenarian ratio; PM10 (particles with diameters of 10 μm or less) concentration and coal consumption (CC) per capita decrease the longevity index, and GDP (Gross Domestic Product) per capita prolongs life expectancy at birth, while energy consumption (EC) per capita decreases life expectancy at birth. Further, our findings demonstrate that public health outcomes show clear regional differences in China. Highlights: Association between health outcomes and environment and socio-economy was analysis. Using GWR and SR models to detect the association. High SO2, PM10, CC & EC have negative impact on public health outcomes. Public health outcomes show clear regional differences in China.